Agricultural Productivity and Farmers Welfare Involution (Case Study in Meunasah Pinto Aceh Utara) - ., Nirzalin; Maliati, Nulwita (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTAbundant rice productivity as a result of the success of the modernization of the system, pattern of production and use of seeds are carried by the Indonesian government in agriculture was not automatically change the level of farmers welfare. Based on studies in meunasah Pinto North Aceh District, this article is going to show that the issue of farmers’ welfare is a complex issue strands. At the empirical level narrow land ownership, capital dependence on the elite village economy, changes in the production system of reciprocity into a wage complex obstacles to change farmers’ welfare.In fact, this modernization not only exposes farmers to the issue of involution wellbeing but also directly contribute to the flourishing of social segregation in society as in Meunasah Pinto, North Aceh. As a result, the social insurance obtained by citizens when agricultural production systems is reciprocity now after changing the wage system of social insurance is gone. The high individuality as a new mode of social life also requires farmers to adapt to the problems of their lives increasingly problematic in the midst of well-being that low.Keywords: Farmers, Welfare, modernization of production systems, Meunasah Pinto, North AcehABSTRAKProduksi pertanian yang melimpah sebagai konsekuensi dari keberhasilan modernisasi sistim, pola produksi dan penggunaan bibit unggul tidak secara otomatis dapat mengubah tingkat kesejahteraan petani. Berdasarkan studi di Meunasah Pinto Kabupaten Aceh Utara. Artikel ini hendak menunjukkan kompleksitas persoalan kesejahteraan petani. Dalam tataran empiris, sempitnya lahan,, ketergantungan modal pada elite ekonomi desa dan pergeseran sistim reprositas dalam sistim produksi sebagai akibat dari modernisasi sistim pertanian merupakan hambatan-hambatan mendasar terhadap perubahan kesejahteraan petani. Realitasnya, modernisasi sistim pertanian tidak hanya berakhir pada terjadinya involusi kesejahteraan petani tetapi juga berkontribusi langsung pada terjadinya segregasi sosial pada masyarakat petani Meunasah Pinto, Aceh Utara. Implikasinya, asuransi sosial yang terjalin melalui sistim reprositas pada pelbagai aspek kehidupan termasuk pada sistim produksi pertanian kini hilang. Modernisasi yang diikuti dengan rasionalisasi dalam pola hubungan produksi menyebabkan pola hubungan produksi tradisional yang bersifat komunal dan reprositas berubah menjadi serba upah dan individual. Gaya hidup individual ini menghadapkan para petani pada pelbagai persoalan dalam kehidupan mereka.Kata kunci: Kesejahteraan petani, modernisasi sistim produksi, Meunasah Pinto, Aceh Utara